Departure [videorecording (DVD)] - Steggall, Andrew; Stevenson, Juliet; Lawther, Alex, 1995-; Brossard, Phenix; Cusack, Niamh; Lynch, Finbar (Wolfe, 2017)
An English mother and her teenage son spend a week preparing the sale of their remote holiday house in the South of France. Fifteen-year-old Elliot struggles with his dawning sexuality and an increasing alienation form his mother, Beatrice.